Effectiveness of Product-Differentiated Project-Based Learning (PjBL) Anchored in Kalimas Local Potential in Enhancing 21st Century Skills Among Junior High School Students - Fitria Rahmawati, Rika; Prasetya, Sukma Perdana; Segara, Nuansa Bayu (Universitas Islam Negeri Raden Intan Lampung, 2026)
Students’ motivation and creative thinking skills in Social Studies remain constrained by teacher-centred instruction and limited use of local contextual resources. This study examined whether product-differentiated Project-Based Learning (PjBL) anchored in the economic potential of the Kalimas River improves seventh-grade students’ learning motivation and creative thinking skills more effectively than Discovery Learning. A quasi-experimental non-equivalent control group design involved two intact classes at a private junior high school in Surabaya: an experimental class receiving product-differentiated PjBL (n = 30) and a control class receiving Discovery Learning (n = 30). Data were collected using a validated motivation questionnaire based on Self-Determination Theory and an essay-based creative thinking test grounded in Munandar’s dimensions of fluency, flexibility, originality, and elaboration. After prerequisite tests were fulfilled, data were analysed using N-Gain and one-way MANOVA. MANOVA showed a significant simultaneous difference between groups, p < .001. The experimental class obtained higher gains in learning motivation (pre-test M = 68.5; post-test M = 86.4; N-Gain = 0.57) and creative thinking skills (pre-test M = 55.2; post-test M = 82.6; N-Gain = 0.61) than the control class (motivation N-Gain = 0.26; creative thinking N-Gain = 0.34). Product-differentiated PjBL grounded in the Kalimas local context is more effective than Discovery Learning in concurrently strengthening students’ motivation and creative thinking. The findings support contextual, autonomy-oriented PjBL as a practical strategy for fostering 21st-century competencies in Social Studies within the Merdeka Curriculum.